2018
DOI: 10.1186/s12891-018-2053-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgical margins in atypical Lipomatous Tumours of the extremities

Abstract: BackgroundAtypical lipomatous tumours (ALT) are common adipocytic tumours. Due to their large size and deep-seated location, wide resection might result in severe functional deficits. The question which margins should be aimed is hence discussed controversially.MethodsForty consecutive patients underwent limb-sparing resections. Margins were defined as R0 (wide resection), R1 (marginal resection) or R2 if tumour was left. All patients were followed for evidence of local recurrence or remote metastases. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
2
24
0
2
Order By: Relevance
“…Studies concerning ALT recurrence rates are more often reported in the literature, and as with IML these studies have also shown great variance, ranging from 7.5-22.6% [8][9][10][11][12]. Only a few of these studies calculate a proper LRFS (89-95%) after 5 years [11,12], and only 1 study also calculated a 10-year LRFS of 82% [11], which is in good agreement with our ALT findings. The variance in the reported recurrence rates across the literature might in part be explained by the follow-up regimens used.…”
Section: Resultssupporting
confidence: 89%
“…Studies concerning ALT recurrence rates are more often reported in the literature, and as with IML these studies have also shown great variance, ranging from 7.5-22.6% [8][9][10][11][12]. Only a few of these studies calculate a proper LRFS (89-95%) after 5 years [11,12], and only 1 study also calculated a 10-year LRFS of 82% [11], which is in good agreement with our ALT findings. The variance in the reported recurrence rates across the literature might in part be explained by the follow-up regimens used.…”
Section: Resultssupporting
confidence: 89%
“…Based on typically large size and deep-seated location of the ALTs, wide resection might result in severe functional deficits. Therefore, debate about what type of margins (marginal or wide resection) should be aimed for and whether adjuvant radiotherapy might reduce the risk of local recurrence is still ongoing [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…der lokalen Kontrolle für eine additive RT zeigen (5-Jahres-LRFS [LRFS: lokalrezidivfreies Überleben] 98 vs. 80 %), dieser bezog sich laut Subgruppenanalyse aber lediglich auf Patienten nach R1-Resektionen [42]. Eine Literaturanalyse von Rauh et al [43] fand eine gepoolte Lokalrezidivrate von 7 % nach R0-Resektion sowie von 17 % nach R1-Resektionen. Der Anteil von Dedifferenzierungen in den Rezidiven betrug lediglich 14 % [43].…”
Section: Besonderheiten Bei Liposarkomenunclassified
“…Eine Literaturanalyse von Rauh et al [43] fand eine gepoolte Lokalrezidivrate von 7 % nach R0-Resektion sowie von 17 % nach R1-Resektionen. Der Anteil von Dedifferenzierungen in den Rezidiven betrug lediglich 14 % [43]. Da die meisten Lokalrezidive chirurgisch suffizient behandelt werden können und nur selten einen dedifferenzierten Anteil enthalten, muss die Indikation zur additiven RT daher selbst nach R1-Resektion eines reinen ALT streng gestellt werden [41,44].…”
Section: Besonderheiten Bei Liposarkomenunclassified